Ação neuroprotetora e anti-inflamatória do disseleneto de difenila e exercício de natação em modelo de envelhecimento em ratos - Leite, Marlon Regis (2016)
Aging is a degenerative process that affects virtually all living organisms. The increase in the inflammatory process seems to be one of the main factors that contribute to aging and inflammaging and neuroinflammation in the hypothalamus plays a critical role.This way, the objective of this study was to investigate the effects of a supplemented diet with diphenyl diselenide (PhSe)2 and swimming exercise on changes caused by aging in both blood and hypothalamus of old Wistar rats (27 months). For the first study, the animals were supplemented with (PhSe)2 (1 ppm) in the diet and performed swimming exercise with overload (3% body weight, 20 min / day, 5 days per week). Both (PhSe)2 supplementation as the swimming exercise lasted four weeks. Blood samples were collected for analysis of levels of interleukins pro- and anti-inflammatory. The results of the first study clearly demonstrated the anti-inflammatory effects of (PhSe)2 plus swimming exercise because the serum levels of pro-inflammatory cytokines were decreased in rats of different ages (middle age and old). Furthermore, the anti-inflammatory protein IL-10 was increased in serum of rats of different ages. However old rats that underwent only swimming exercise increased serum levels of proinflammatory cytokines and IL-10 was decreased, suggesting that the swimming exercise protocol was exhaustive for these animals. There was no change in blood of old rats supplemented only with (PhSe)2 . These results demonstrated that a diet supplemented with (PhSe)2 and swimming exercise affected serum levels of pro- and anti-inflammatory cytokines dependent of age of the animals. For the second study, animals received supplementation (PhSe)2 simmilary to first study (1 ppm). However, in view of the pro-inflammatory effects of swimming exercise observed in the first study, the overhead used was reduced (1% of body weight, 20 min / day, 5 days per week). Again, both supplementation with (PhSe)2 and swimming exercise lasted 4 weeks. The Western blotting assay was performed to evaluate the levels of proteins involved in the activation of glial cells, apoptosis and neuroprotection. Furthermore, the imunohistoquinica assay was performed to confirm the activation of astrocytes. In the second study, a decrease in the levels of glial cell activation markers (GFAP and IBA-1) was observed in the hypothalamus of aged rats supplemented with (PhSe)2 and that performed swimming exercise. Furthermore, JNK phosphorylation, a kinase involved in the inflammatory response and apoptosis, was decreased. An anti-apoptotic effect by the supplementation with (PhSe)2 and swimming exercise was observed since the levels of NeuN were increased as well as anti-apoptotic protein Bcl2 in the hypothalamus of old rats. Reinforcing this anti-apoptotic effect, the levels of pro-caspase-3 and cleaved PARP were increased and decreased respectively. Increased levels of mature BDNF and phosphorylated Akt, two proteins involved in cell survival, were increased by supplementation with (PhSe)2 and swimming exercise. These results demonstrated the beneficial effects of supplementation (PhSe)2 and swimming exercise on age-related changes.